(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Armed Forces personnel suffer from various patterns of injuries during their military training activities which may lead to considerable mortality & morbidity. The high incidence of injuries places a substantial burden on the health care delivery system. Successful treatment outcome and modifications can reduce the operational, fiscal, and health impact of these problems. Objective: To find out the types, causes and morbidity pattern of common injuries received by the members of Bangladesh Armed Forces during their military activities. Methods: This is a descriptive retrospective study carried out to explore the injuries amongst Bangladesh Armed Forces personnel due to military duties. The study population (193) included all injured indoor cases treated in Combined Military Hospital (CMH) Dhaka during the period of January 2009 to December 2009. Data was collected by reviewing the case sheets of patients and analyzed with the help of SPSS Version 11.5. Results: Numbers of Injured subjects amongst the Army personnel were 132(68.4%) followed by 34(17.6%) in Navy and 27(14%) in Air Force. Among them 82(42.5%) belonged to fighting group, 50(25.9%) supporting and 61(31.6%) service group. Knee injury constituted the highest number of patients i.e. 43(22%), followed by 43 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 33(17%) Armand 25(13%) foot injuries. About one fourth, 53(27.5%) cases sustained injury in sports ground followed by 50(25.9%) in operation area and 28(14.5%) in training ground. Physical training events PT/Drill caused maximum injury 7(3.6%) followed by crossing 6ft wall 5(2.6%), horizontal rope 4(2.1%). Maximum duration of hospital stay among the cases were 1-2 weeks in 65(33.7%) followed by 3-4 weeks in 56(29%) and 1-3 months in 41(21.2%) cases. Eighty two (42.5%) injured cases suffered for 3 to 6 months followed by 43(24.4%) for 6 months to1 year. Out of all cases 72(37.3%) were recommended for medical category C, 2(1%) for category B, 11(5%) were Medically Boarded Out (MBO). Conclusion: The study revealed that musculoskeletal injuries especially in knee, foot, shoulder, forearm, ankle, lower leg and patella are prevalent in armed forces personnel. The high incidence of injuries places a substantial burden on the health care delivery system and leads to many lost training days. Careful study and analysis in this regard definitely will explore new dimension to prevent and combat this preventable health burden. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21825 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013